Precision approach to diabetic peripheral neuropathy: modified nerve decompression surgery and MNGF treatment - Zhang, Yanji; Song, Hehua; Jian, Yang; Cai, Silang; Deng, Chengliang; Wei, Zairong (Frontiers in Medicine, 2025)
BackgroundDiabetic peripheral neuropathy (DPN) is a common and debilitating complication of diabetes, often resulting in pain, sensory loss, and lower limb ulcers. While traditional nerve decompression (ND) surgery can alleviate symptoms, it is associated with several limitations, including excessive surgical trauma, postoperative fibrosis, and limited efficacy in advanced cases. To address these challenges, this study aimed to precisely target anatomical sites of peripheral nerve compression identified through cadaveric dissection, perform selective decompression to minimize nerve injury, and investigate the therapeutic potential of combining modified ND with murine nerve growth factor (MNGF) to enhance clinical outcomes.MethodsIn this assessor-blinded, three-arm exploratory randomized controlled trial, 42 patients with confirmed lower limb DPN were randomly assigned to one of three groups: traditional ND (n = 12), modified ND (n = 16), or modified ND combined with MNGF therapy (n = 14). Modified ND involved selective decompression of tendon-like structures without extensive epineurial dissection. Clinical outcomes were assessed preoperatively and at 4 and 12 weeks postoperatively using motor nerve conduction velocity (MNCV), Toronto Clinical Scoring System (TCSS), visual analog scale (VAS), two-point discrimination (2-PD), 10 g monofilament test, and ultrasound-based nerve cross-sectional area (CSA).ResultsAll groups showed significant improvements in MNCV, TCSS, VAS, 2-PD, and sensory function after treatment (p < 0.05). The modified ND + MNGF group demonstrated the greatest enhancements in nerve conduction and clinical scores, with significant intergroup differences compared to the traditional ND group (p < 0.05). Additionally, the modified ND technique reduced surgical trauma and postoperative complications. No severe adverse events were reported.ConclusionModified ND surgery, particularly when combined with MNGF administration, may offer a safe and minimally invasive treatment option for lower-limb DPN. Further validation in larger, multicenter trials is warranted.